Acute pancreatitis as a risk factor of chronic pancreatitis and pancreatic cancer. An overview - Solil, David; Dítě, Petr; Šenkyřík, Michal; Bojková, Martina; Kianička, Bohuslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
This is an overview of relation between acute and chronic pancreatitis and between acute pancreatitis and pancreatic cancer. Acute pancreatitis and recurrent acute pancreatitis are an etiological factor of chronic pancreatitis. Population-based studies have calculated the risk of acute recurrent pancreatitis after the first attack of acute pancreatitis to be 20% and development of chronic pancreatitis after first attack of acute pancreatitis is 10%. An important risk factor is tobacco smoking. Acute and chronic pancreatitis are risk factors for pancreatic cancer. The risk of acute pancreatitis is related to the number of recurrences of acute pancreatitis, but not the etiology of acute pancreatitis. Acute pancreatitis, as well as chronic pancreatitis, are risk factors for pancreatic cancer. After an attack of acute pancreatitis or recurrent acute pancreatitis a patient should be regarded as a high risk.
Keywords: rizikové faktory; Pancreatitis; kouření; Pancreatic Neoplasms; akutní nemoc; Risk Factors; Pancreatitis, Chronic; lidé; Acute Disease; Recurrence; pankreatitida; Smoking; recidiva; nádory slinivky břišní; chronická pankreatitida; Humans